PENGARUH KEMAMPUAN KOMUNIKASI INTERPERSONAL PENDAMPING SOSIAL DENGAN ANGGOTA KELOMPOK USAHA BERSAMA TERHADAP KINERJA USAHA EKONOMI PRODUKTIF DI KOTA BANJARMASIN - Muhammadun Muhammadun; Rahmi Widyanti; Basuki Basuki (AL-ULUM : Jurnal Ilmu Sosial dan Humaniora, 2019)
Sosial assistant interpersonal communication is a process of interpersonal interaction is done by social assistant with members of the Business Group (KUBE) in developing productive economic activities in the city of Banjarmasin by using verbal and non-verbal communication. Thesis research method is quantitative research. Place of research conducted in the city of Banjarmasin.The research objective was to determine whether there is influence interpersonal communication skills are built between social companion with members UsahaBersama Group (KUBE) in developing productive economic activities in the city of Banjarmasin.Our research found that there is a significant relationship between interpersonal communication skills with a social companion KUBE members in developing productive economic activities in the city of Banjarmasin through a cognitive approach. There is influence between interpersonal communication skills with a social companion KUBE members in developing productive economic activities in the city of Banjarmasin through emotional approach. There is a relationship between the ability -komunikasi interpersonal social companion with KUBE members in developing productive economic activities in the city of Banjarmasin fun approach.Suggestion of this research to the Social Welfare Office of South Kalimantan Province should be better in fostering the social companion and member of the Joint Business Group (KUBE) that will be established good cooperation in developing productive economic activities that already exist for more advanced and developed. Need further research to determine other factors that could affect the development of productive economic activities of members of the Joint Business Group (KUBE). Keywords: Interpersonal Communication, Member of KUBE, Banjarmasin